PENGARUH ACTIVITY SUPPORT TERHADAP AKTIVITAS RUANG PUBLIK PADA MALAM HARI DI KORIDOR JALAN GAJAH MADA AMLAPURA - I Dewa Gede Wirasa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
Activity support is a function and support activity that can strengthen public spaces in a city. The road corridor as a public open space is a place to accommodate these activities and functions. The phenomenon that occurs in the Jalan Gajah Mada-Amlapura corridor is that public activities at night are quiet and limited. This condition shows that the city design elements have not yet functioned optimally, one of which is activity support which should be able to strengthen public spaces in the form of roads. As a result, the city seems to have lost its character and identity, so efforts and strategies are needed to restore it. The importance of fostering public activity at night has economic benefits for society and the government in addition to social and cultural benefits. The purpose of this research is to analyze the factors causing the current limited activity support and its effect on public space activities at night in the corridor of Jalan Gajah Mada Amlapura. The hope is to support the formation of a more vibrant and dynamic city character. The research method used is a qualitative method with a case study approach. Data collection techniques were carried out through direct observation and study of related documents. Primary data was obtained through field observations, secondary data was obtained from articles and journals and literature books. Data analysis is carried out by organizing, selecting and describing data, synthesizing, and drawing conclusions. Furthermore, the data is presented in the form of tables, pictures and narrative descriptions. The results of the study show that the causes of the limited activity support are the shape and location of the area, area characteristics, parking elements, diversity of activities, and the presence of pedestrian areas. This condition affects the lack of public activity in the corridor of Jalan Gajah Mada Amlapura so that it has not been able to support the formation of the character of the city.